Estimating fuel-efficiency while accounting for dynamic fleet management: Testing the effects of fuel price signals and fleet rollover. (June 2021) - Oliveira, Alessandro V.M.; Narcizo, Rodolfo R.; Caliari, Thiago; Morales, Maurício A.V.; Prado, Rafael
Abstract: Fuel efficiency has become one of the most important policy goals for airline operations management. This study develops an econometric model to estimate airlines' fuel burn determinants, aiming to test the hypothesis of fuel price signals on carriers' incentives for energy-saving efforts. We propose a novel high-dimensional sparse IV-LASSO method to account for airline dynamic fleet management. Our model also provides controls for thousands of nuisance factors related to route direction, airway congestion, and aircraft model specificities, allowing for flexible time-varying unobserved effects of flight stages. The results show that energy intensity reduction induced by price increases was observed 3–4 years earlier, possibly due to fleet rollover and fleet modernization. Furthermore, although new competition may create incentives for improved fuel management to control costs, our results suggest that the overall effect of market deconcentration is unclear and may produce the unintended consequence of worse performance, as measured in some key fuel efficiency dimensions.